An Improved HT Algorithm on Straight Line Detection Based on Freeman Chain Code - Li Chao; Wang Zhong; Li Lin (2009 2nd International Congress on Image and Signal Processing, 2009)
Straight line detection has a great significance in the area of image processing, the conventional Hough transform (HT) algorithm used to detect a straight line has to process a large mount of data, so it needs more storage space and the calculation time is too long. This paper presents an improved HT algorithm on straight line detection based on Freeman chain code. It extracts the Freeman chain codes of the pixels in the sub-line segment elements, and transforms them to the angle codes in the polar coordinates space. Constraint the angle searching area of the pixels, so that the calculation speed can be improved. Experiment shows that compared with the Standard Hough transform (SHT), the calculation time of this algorithm reduces to 1/28 ~ 1/75.